Comparison of simulation software and contrastive training on ECG interpretation competence in newly graduated nurses - Kabiri, Zahra; Masoudi, Reza; Kheiri, Soleiman; Etemadifar, Shahram (Frontiers in Medicine, 2025)
BackgroundImproving the ability of nurses to interpret ECG and diagnose pathological disorders can be effective in preventing the complications of arrhythmias. Therefore, two of the most important indicators of nursing performance among newly graduated nurses for making clinical decisions are clinical competence and critical thinking. Therefore, this study was conducted to compare the effect of contrastive training and simulation software on the level of critical thinking and clinical competence in newly graduated nurses.PurposeThis quasi-experimental study was conducted in Shahrekord (Iran) to compare the effect of contrastive training and simulation software on the level of critical thinking and clinical competence in newly graduated nurses.MethodsA total of 66 newly graduated nurses participated in the study in two intervention and control groups. Inclusion criteria included providing informed consent to participate in the study, holding a bachelor’s degree in nursing, and having work experience of fewer than 24 months. The fundamentals of electrocardiogram were taught through one session, and then in the contrastive training group, in 5 sessions of 35 min, and in the software group. Data were collected before, immediately after, and 3 months after the intervention with the Clinical Competency and Critical Thinking Questionnaire in electrocardiogram interpretation.ResultsThe mean pre-intervention score of clinical competence was 6.36 ± 1.98 in the software group and 6.36 ± 2.50 in the contrastive training group, and immediately after the intervention 9.06 ± 1.48 in the software group and 9.74 ± 1.53 in the contrastive training group. Three months after the intervention, the mean score was 8.27 ± 1.89 in the software group and 8.87 ± 1.78 in the contrastive training group. There was a significant difference among all steps (p < 0.001). Before the intervention, the mean score of critical thinking was 5.61 ± 2.86 in the software group and 7.84 ± 3.15 in the contrastive training group, and immediately after the intervention 9.27 ± 1.93 and in the coping training 11.26 ± 2.90, and 3 months after the intervention 7.97 ± 2.17 and 10 ± 2.68 in the software group. The difference in scores on both variables at all intervals between the two groups was significant (p < 0.001). In both groups, there was a significant increase in both variables at all intervals, but the mean score was higher in the contrastive training group than in the simulation software group.ConclusionBoth contrastive training and simulation software promote critical thinking and clinical competence in interpreting electrocardiograms among newly graduated nurses, but the effects of training are mitigated over time and it is, therefore, necessary to take into consideration a longer training program using a simulation approach and contrastive training, especially in case of contrastive training.